PERANAN DESAIN KOMUNIKASI VISUAL SEBAGAI PENDUKUNG MEDIA PROMOSI KESEHATAN - Yosef Yulius (Besaung : Jurnal Seni Desain dan Budaya, 2016)
media. With a health promotion media, the public will more easily understand the scope of health and disease that is common in people's lives. Implementation of visual communication design to the health promotion media is important, so that all the information given to the public can be accepted in accordance with the achievement to be achieved. The application of the science of visual communication design in health promotion media is expected to be able to improve the quality of health promotion media as an information medium that is communicative and readily accepted by the public. Key words :Health promotion, awareness, media, promotion, visual communication design.